Nanomaterials and Energy Storage in a Glance: a Review - Abdallh, Mustafa; Hussain, Zainab; Thamer, Hamsa; Abd Ali, Ali; Yousif, Emad; Mohammed, Salam (Al-Nahrain Journal of Science, 2021)
The challenge to provide a powerful instrument with a high energy conversion is of a great importance to our modern society, not only in terms of conversion but in high-capacity storage derived by the increase for energy demand. In addition, the environmental impact of these new technologies to create a green and sustainable environment. One of these green technologies is the use of dye-sensitized solar cells to produce energy and lithium-ion batteries to store the generated energy. The need for high electronic mobility and high surface volume and activity, nano metal oxide was investigated as alternative or a new material in generation and conversion of energy. For this purpose, many metal oxides were explored especially Zinc oxide (ZnO) and titanium oxide (TiO2) due to their electronic characteristics.